Durable membrane and its preparation and use

By adhering poloxamer to the polyolefin microporous sheet and forming a water-wettable filter membrane through photoinitiation grafting technology, the problems of insufficient durability of the filter membrane and difficulty in recovering solutions in the prior art are solved, and high efficiency is achieved , environmentally friendly filtering effect.

CN115151336BActive Publication Date: 2025-02-11HYDROXSYS HOLDING LIMITED
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202080080312.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-10
Filing Date
2020-10-02
Publication Date
2025-02-11
Estimated Expiration
2040-10-02

AI Technical Summary

Technical Problem

The existing filter membranes are not durable when using chemically aggressive cleaning solutions, making them difficult to achieve in-situ cleaning, and the recycling and reuse of aqueous cleaning solutions has problems of cost and environmental impact.

Method used

Poloxamer is used to form a water wettable filter membrane that is adhered to the polyolefin microporous sheet by covalent bonding or grafting. The filter membrane is formed in the presence of a crosslinking agent by photo-induced grafting technology, which improves the durability and flux of the membrane.

Benefits of technology

A filter membrane that maintains high durability and flux under chemically aggressive conditions is achieved, enabling in-situ cleaning and recycling of aqueous cleaning solutions, reducing costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005130098620000201
    Figure GDA0005130098620000201
  • Figure GDA0005130098620000202
    Figure GDA0005130098620000202
  • Figure GDA0005130098620000211
    Figure GDA0005130098620000211
Patent Text Reader

Abstract

Described herein are filter membranes comprising a microporous sheet of polyolefin grafted with a poloxamer. In one embodiment, the poloxamer is marketed under the trade name PLURONIC TM P-123 is supplied and the polyolefin is poly(ethylene). The membrane offers the advantage of being resistant to cleaning agents used in clean-in-place schemes and can be used to remove particles from these aqueous feed streams.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to durable filtration membranes, filtration membrane modules comprising such membranes and their use in recovering water from feed streams. In particular, the present invention relates to durable filtration membranes and their use in recovering water from feed streams, wherein the membranes need to be cleaned in situ periodically. Background Art

[0002] The use of grafting to modify the surfaces of films, sheets and molded articles formed from polyolefins is well known. For example, a publication by Tazuke and Kimura (1978) discloses the use of benzophenone as a sensitizer for photografting onto poly(propylene), poly(ethylene) and several other polymer films. In this publication, it is noted that the choice of solvent and sensitizer is very important.

[0003] A publication by Ang et al. (1980) discloses an irradiation procedure in which the sensitizer is dissolved in the monomer solution and can be used to photosensitize the copolymerization of styrene, 4-vinylpyridine and methyl methacrylate to poly(propylene) in high yields. The publication again states that the reaction was found to be very specific for certain types of sensitizers.

[0004] A publication by Ogiwara et al. (1981) discloses photografting onto poly(propylene) and low density poly(ethylene) (LDPE) films on which a sensitizer is pre-coated. The sensitizer coated on the film enables easy grafting of vinyl monomers such as methyl methacrylate, acrylic acid and methacrylic acid with high yield. Grafting is conveniently performed in aqueous solution in a liquid phase system using the hydrophilic monomers acrylic acid and methacrylic acid.

[0005] A publication by Allmer et al. (1988) discloses the modification of the surface of LDPE, high density poly(ethylene) (HDPE) and polystyrene by grafting with acrylic acid. The grafting is carried out in the gas phase and increases the wettability of the polymer. It was observed that acetone was able to initiate the grafting and that the emission promoted and directly grafted onto the surface. A subsequent publication by Allmer et al. (1989) discloses the grafting of the surface of LDPE with glycidyl acrylate and glycidyl methacrylate by photoinitiation. Acetone and ethanol were used as solvents, with acetone producing slightly more grafting at the surface.

[0006] The publications of Yao and Ranby (1990a, 1990b and 1990c) disclose, inter alia, a process for the continuous photoinitiated graft copolymerization of acrylamide and acrylic acid onto the surface of HDPE tape films. The process is carried out under a nitrogen environment using benzophenone as a photoinitiator. It is noted that pre-immersion is very important for efficient photografting within a short irradiation time. The application of this pre-immersion photografting process to poly(ethylene terephthalate) (PET) is also disclosed. In this context, acetone was found to be a slightly better solvent than methyl ethyl ketone and methyl propyl ketone. When applied to the continuous process of photochemically induced graft polymerization of acrylamide and acrylic acid on the surface of poly(propylene) (PP) fibers under a nitrogen environment, the optimal concentrations of monomers and initiators in the pre-immersion solution were determined.

[0007] Publications by Kubota and Hata (1990a and 1990b) disclose studies of the location of methacrylic acid chains introduced into poly(ethylene) films by liquid and gas phase photografting, as well as comparative examinations of the photografting behavior of benzil, benzophenone, and benzoin ethyl ether as sensitizers. In these latter studies, poly(methacrylic acid) was grafted onto initiator-coated LDPE films.

[0008] A publication by Edge et al. (1993) discloses the photochemical grafting of 2-hydroxyethyl methacrylate (HEMA) onto LDPE films. Liquid phase processes are used to produce materials with increased wettability.

[0009] A publication by Singleton et al. (1993) discloses a method for preparing a polymer sheet wettable by aqueous solvents and useful as an electrode separator in an electrochemical device. The polymer sheet is formed from fibers comprising only poly(propylene) and is distinct from a membrane formed from a microporous polymer sheet.

[0010] A publication by Zhang and Ranby (1993) discloses the photochemically induced graft copolymerization of acrylamide onto the surface of PP films. Of the three aliphatic ketones tested, acetone appeared to be the best solvent.

[0011] Publications by Yang and Ranby (1996a and 1996b) disclose factors that influence the photografting process, including the effect of far UV radiation (200 to 300 nm). In these studies, benzophenone was used as a photoinitiator and LDPE film was used as a substrate. Added water appeared to favor the photografting polymerization of acrylic acid on the surface of the polyolefin, but acetone was shown to have a negative effect due to the different solvation of poly(acrylic acid) (PAA).

[0012] The publication by Hirooka and Kawazu (1997) discloses alkaline separators prepared from sheets of poly(ethylene)-poly(propylene) fibers grafted with unsaturated carboxylic acids. Furthermore, the sheets used as substrates in these studies are different from membranes formed from microporous polymer sheets.

[0013] The publication by Xu and Yang (2000) discloses studies on the mechanism of gas phase photografting of acrylic acid onto LDPE.

[0014] A publication by Shentu et al. (2002) discloses a study of factors affecting photografting on LDPE, including the concentration of monomers.

[0015] A publication by El Kholdi et al. (2004) discloses a continuous process for grafting acrylic acid onto LDPE from an aqueous monomer solution. A publication by Bai et al. (2011) discloses the preparation of a hot melt adhesive grafted with low density poly(ethylene) (LDPE). The adhesive was prepared by UV photografting acrylic acid onto LDPE using benzophenone as a photoinitiator.

[0016] The publication by Choi et al. (2001) states that graft polymerization is recognized as a general method for modifying the chemical and physical properties of polymeric materials.

[0017] A publication by Choi (2002) discloses a method for producing acrylic graft polymers on the surface of a polyolefin article, the method comprising the steps of immersing the article in an initiator solution of a volatile solvent, allowing the solvent to evaporate, then immersing the article in a solution of an acrylic monomer, and then subjecting the article to ultraviolet light exposure in air or an inert atmosphere. Acrylic acid is used as the acrylic monomer in each of the examples disclosed in the publication, although it is contemplated that equivalent amounts of methacrylic acid, acrylamide, and other acrylic monomers are used.

[0018] The publication of Choi (2004) discloses the use of "ethylenically unsaturated monomers" in graft polymerization. These other monomers are disclosed as monomers that polymerize into thermoplastic polymers by addition polymerization and have hydrophilicity due to the presence of carboxyl (-COOH), hydroxyl (-OH), sulfonyl (SO3), sulfonic acid (-SO3H) or carbonyl (-CO) groups. No experimental results are disclosed regarding the chemical and physical properties of graft polymers prepared by the process using these other monomers.

[0019] A publication by Choi (2005) discloses nonwoven sheets of polyolefin fibers, wherein the opposing surfaces of the sheet are hydrophilic due to acrylic acid graft polymerization. The nature of the sheet is asymmetric, and the ion exchange coefficients of the two surfaces are different. The method for preparing these asymmetric acrylic acid graft polymerized nonwoven polyolefin sheets comprises the steps of immersing the substrate in a benzophenone (photoinitiator) solution, drying, then immersing the substrate in an acrylic acid solution, and then irradiating with ultraviolet light (UV). The irradiation can be carried out when the surface is in contact with air or an inert atmosphere.

[0020] Gao et al. (2013) discloses a method for preparing a radiation-crosslinked lithium-ion battery separator. In one example, a porous polyethylene film is immersed in a dichloromethane solution of benzophenone and triallyl cyanurate. The immersed film is dried at room temperature and then immersed in a 30°C water bath and irradiated on both sides for three minutes using a high-pressure mercury lamp.

[0021] The publication by Jaber and Gjoka (2016) discloses the use of monomers with one or more anionic, cationic or neutral groups to graft ultra-high molecular weight polyethylene microporous membranes. The publication states that the authors have found that molecules can be grafted onto the surface of an asymmetric porous ultra-high molecular weight polyethylene membrane using an ultraviolet radiation energy source. The grafted membrane is believed to be useful for removing charged contaminants from liquids.

[0022] Most of these prior art methods aim to improve the adhesion, biocompatibility, printability or wettability of substrate surfaces using photoinitiated polymerization. These methods are distinguished from the use of UV-initiated grafting with exogenously prepared preformed polymers to modify the permeability of hydrophobic microporous polyolefin matrices.

[0023] A publication by Schmolka (1973) discloses the preparation of polyoxyethylene-polyoxypropylene block polymers represented by the formula:

[0024] HO(C2H4O) b (C3H6O) a (C2H4O) b H

[0025] wherein a is an integer such that the hydrophobic matrix represented by (C3H6O) has a molecular weight of at least 2,250, and b is an integer from about 8 to 180 or more. These block polymers are used to prepare solid or semisolid colloids containing large amounts of liquid - "gels" or "hydrosols" (where the liquid is water), which are particularly useful in the formulation of cosmetic and pharmaceutical compositions for topical application. These nonionic triblock copolymers, known as poloxamers, are available under a number of trade names, including ACCLAIM TM 、ADEKANOL TM ANTAROXTM 、BASOROL TM 、BLAUNON TM ETHOX TM 、KOLLIPHOR TM ,LUTROL TM MEROXAPOL TM , PLURIOL TM 、PLURONIC TM and SYNPERONIC TM The properties of poloxamers are determined by the ratio and size of the integers a and b. Triblock copolymers in which the order of the polyoxyethylene and polyoxypropylene blocks is reversed are also supplied under these trade names. These "reverse" triblock copolymers may be identified by the use of the letter "R" and should not be referred to as "poloxamers."

[0026] A publication by Wang et al. (2006) discloses the formation of membranes from blends of polyethersulfone and different triblock copolymers by a phase inversion method. It was observed that the water flux measured on the membranes depended on the triblock copolymer structure rather than the content. For example, it was observed that the water flux of the membranes made of PLURONIC TM The water flux of the membrane formed by the blend of PLURONIC 123 (50.161 LMH) was less than the water flux observed in the polyethersulfone control membrane (109.081 LMH). TM The water flux of the membrane formed by the blend of F68 (218.28 LMH) was higher than that of the control membrane.

[0027] The publication of Liu et al. (2014) discloses the preparation of microporous membranes with microstructured surfaces for separating oil from water-in-oil / water emulsions. In the method for preparing the membrane, polyoxyethylene-polyoxypropylene-polyoxyethylene (F127) is used as an additive for preparing a uniform solution of a polymer in a solvent. The polymer is selected from polyvinylidene fluoride (PVDF), polysulfone (PSf), polyethersulfone (PES), polyacrylonitrile (PAN), polyvinyl chloride (PVC), polylactic acid (PLA), polyimide (PI), polypropylene (PP) or cellulose acetate, and the solvent is selected from chloroform (CHCl3), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), triethyl phosphate (TEP), trimethyl phosphate (TMP), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), dibutyl phthalate (DBP), dioxane, phenylacetone, diphenyl ether and one or more mixtures thereof.

[0028] The publication by Yang et al. (2014) discloses a composite polymer electrolyte for lithium-polymer batteries. The composite material consists of a mesoporous modified silica filler dispersed in a poly(vinylidene fluoride-hexafluoropropylene) matrix. TM 123 (Aldrich) was used to prepare mesoporous silica fillers.

[0029] Guo et al. (2015) discloses microporous materials for microfiltration and ultrafiltration membranes. The microporous material comprises finely divided particles, such as water-insoluble silica fillers, distributed throughout a matrix such as poly(ethylene). The material further comprises a network of interconnected pores and can be further processed according to the desired application. In this further processing, triblock copolymers based on poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) can be used as hydrophilic coatings, although polymers containing tertiary amine functional groups are preferred. Without wishing to be bound by theory, it is claimed that the components of the coating can interact with the silica particles in the filler of the microporous material and adjust the surface energy, thereby affecting wettability. Covalent bonding of the hydrophilic coating, such as that achievable by grafting, is not disclosed.

[0030] A publication by Cheng et al. (2017) discloses the use of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymers as "structure directing agents" in the preparation of mesoporous composite membranes. The structure directing agent is used with one or more of a catalyst and a precursor compound such as tetraethyl orthosilicate, titanium tetrachloride, n-butyl titanium acetate, isopropyl titanium, dizinc phthalate acetate, tin esters, and niobates to provide a mesoporous composite membrane.

[0031] The publication by Carter et al. (2018) discloses triblock copolymer PLURONIC as a solvent for pore-filled regenerated cellulose membranes during initiator fixation TM Evaluation of L64. In this case, glycerol was determined to be a more efficient pore-filling solvent.

[0032] Most of these prior art methods use the triblock copolymer as an aid in preparing the membrane, rather than as an integral component.

[0033] The publications of Bolto et al. (2009) provide a review of the disclosures involving crosslinking of poly(vinyl alcohol) (i.e., PVA). These publications include those involving crosslinking methods and grafting of PVA onto support membranes, including porous hydrophobic membranes such as poly(ethylene) and poly(propylene).

[0034] The publication of Linder et al. (1988) discloses a semipermeable composite membrane comprising a membrane of a modified PVA or PVA-copolymer on a porous support. Suitable support materials need to be water-insoluble and can be selected from, for example, polyacrylonitrile, polysulfone, polyamide, polyolefins such as poly(ethylene) and poly(propylene), or cellulose.

[0035] Exley's publication (2016) discloses an asymmetric composite membrane consisting of a cross-linked poly(etheretherketone) membrane adhered to a grafted microporous poly(ethylene) sheet. The microporous poly(ethylene) is obtained by photoinitiated grafting with vinyl monomers to provide a hydrophilic sheet.

[0036] The publication by Craft et al. (2017) discloses an improvement to the asymmetric composite membrane disclosed in the publication by Exley (2016). The improved asymmetric composite membrane comprises a poly(vinyl alcohol) polymer crosslinked with a crosslinking agent (e.g., divinylbenzene) coated on a crosslinked poly(etheretherketone) membrane adhered to a grafted microporous poly(ethylene) sheet. The improvement lies in the selectivity of the asymmetric composite membrane obtained.

[0037] Equipment used for beverage and food processing requires regular cleaning. Cleaning may be necessary due to fouling caused by nonspecific adsorption or deposition of proteins, or to avoid microbial contamination of processed beverages or foods. If the filter membrane can be cleaned in situ, the efficiency of equipment operation can be achieved. The aqueous cleaning solutions used in these cleaning procedures are chemically aggressive (acidic, alkaline, hypochlorite, peroxide, etc.). After use, the waste liquid, which usually contains particles from the cleaning operation, needs to be disposed of, resulting in increased costs and potential damage to the environment.

[0038] The ability to recycle and reuse aqueous cleaning solutions without compromising the efficacy of the cleaning operation would be advantageous, but there are many challenges. Any filter membrane used to separate particles from aqueous solutions must be durable, i.e., able to withstand all chemically aggressive cleaning solutions. Second, the filter membrane must be capable of use in a compact configuration, such as a spiral wound filter assembly, and provide a sufficiently high flux to make reuse of the cleaning solution practical in a commercial setting.

[0039] It is an object of the present invention to provide filtration membranes suitable for use in these and other situations, or at least to provide a useful choice in the selection of filtration membranes for use in these and other situations. Summary of the invention

[0040] In a first aspect, a water-wettable filter membrane comprising a poloxamer adhered to a substrate consisting of a microporous sheet of polyolefin is provided. The poloxamer is adhered to a preformed microporous sheet of polyolefin. The poloxamer is adhered to the polyolefin matrix of the preformed microporous sheet by the formation of covalent bonds between the two polymers. The covalent bonds can be formed directly between the poloxamer and the polyolefin or indirectly through a crosslinking agent.

[0041] Preferably, the poloxamer is attached to the substrate by grafting. Most preferably, the poloxamer is attached to the substrate by photoinitiated grafting. In this case, photoinitiated grafting will be understood to encompass the formation of covalent bonds initiated by irradiation with ultraviolet (UV) light, preferably UVC light, in the presence of a suitable photoinitiator. Suitable photoinitiators are type II photoinitiators, such as benzophenone (benzophenone; BP). Photoinitiated grafting is advantageously carried out in the presence of a crosslinking agent. Suitable crosslinking agents are low molecular weight divinyl compounds. Low molecular weight divinyl compounds are compounds having a molecular weight of less than 150 g mol -1 Those with molecular weights such as divinylbenzene (DVB).

[0042] Preferably, the poloxamer is a polymer having the following structure:

[0043] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0044] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90. Most preferably, the poloxamer is equivalent to that sold under the trade name PLURONIC TM P-123 (Sigma-Aldrich) is a triblock copolymer. It should be understood that for the triblock copolymers sold under the trade name PLURONIC TM A polymer sold as P-123 (Sigma-Aldrich) with m being 20 and n being 70.

[0045] Preferably, the polyolefin is poly(ethylene) or poly(propylene). More preferably, the polyolefin is poly(ethylene). Most preferably, the polyolefin is unprocessed poly(ethylene).

[0046] In a first embodiment of the first aspect, there is provided a water wettable filter membrane consisting of a microporous sheet of grafted poly(ethylene), wherein the graft comprises a poloxamer having the structure:

[0047] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0048] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90.

[0049] In a second embodiment of the first aspect, there is provided a water wettable filter membrane composed of a microporous sheet of grafted poly(ethylene), wherein the graft comprises divinylbenzene and a poloxamer having the structure:

[0050] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0051] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90.

[0052] In a second aspect, there is provided a water-wettable filter membrane comprising a microporous sheet of grafted polyolefin, wherein the polyolefin is grafted with a mixture of preformed polymers comprising a poloxamer having the structure:

[0053] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0054] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90.

[0055] Preferably, the blend of preformed polymers comprises a poloxamer and poly(4-vinylbenzene sulfonic acid).

[0056] Preferably, the blend of preformed polymers is adhered to the substrate by grafting. Most preferably, the blend of preformed polymers is adhered to the substrate by photoinitiated grafting. In this case, photoinitiated grafting will be understood to encompass the formation of covalent bonds initiated by irradiation with ultraviolet (UV) light, preferably UVC light, in the presence of a suitable photoinitiator. Suitable photoinitiators are type II photoinitiators, such as benzophenone (benzophenone; BP). Photoinitiated grafting is advantageously carried out in the presence of a crosslinking agent. Suitable crosslinking agents are low molecular weight divinyl compounds. Low molecular weight divinyl compounds are compounds having a molecular weight of less than 150 g mol -1 Those with molecular weights such as divinylbenzene (DVB).

[0057] Preferably, the blend of preformed polymers comprises a poloxamer having the following structure:

[0058] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0059] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90. Most preferably, the poloxamer is equivalent to that sold under the trade name PLURONIC TM P-123 (Sigma-Aldrich) is a triblock copolymer. It should be understood that for the triblock copolymers sold under the trade name PLURONIC TM A polymer sold as P-123 (Sigma-Aldrich) with m being 20 and n being 70.

[0060] Preferably, the polyolefin is poly(ethylene) or poly(propylene). More preferably, the polyolefin is poly(ethylene). Most preferably, the polyolefin is unprocessed poly(ethylene).

[0061] In a first embodiment of the second aspect, there is provided a water wettable filter membrane consisting of a microporous sheet of grafted poly(ethylene), wherein the graft consists of a blend of preformed polymers comprising a poloxamer having the structure:

[0062] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0063] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90.

[0064] In a second embodiment of the second aspect, there is provided a water wettable filter membrane consisting of a microporous sheet of grafted poly(ethylene), wherein the graft consists of a blend of divinylbenzene and a preformed polymer comprising a poloxamer having the structure:

[0065] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0066] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90.

[0067] It is contemplated that in the first or second embodiment of the first or second aspect, poly(propylene) may replace poly(ethylene).

[0068] Preferably, the filter membrane of the first or second aspect is capable of separating micro-sized particles from an aqueous carrier. The micro-sized particles can be abiotic or biological, including bacterial cells. More preferably, the membrane of the first or second aspect provides an aqueous carrier flux greater than 25LMH at a pressure of 5 bar. Most preferably, the aqueous carrier is a used cleaning solution.

[0069] Preferably, the filter membrane of the first or second aspect is a semi-permeable membrane.

[0070] In a third aspect, there is provided a composite membrane comprising a film of at least partially cross-linked poly(vinyl alcohol) adhered to a hydrophilized microporous sheet of polyolefin. Preferably, prior to the adhesion of the poly(vinyl alcohol) film, the polyolefin of the hydrophilized microporous sheet has been grafted with a preformed poly(4-vinylbenzenesulfonic acid) or poloxamer or a blend thereof. More preferably, prior to the adhesion of the poly(vinyl alcohol) film, the polyolefin of the hydrophilized microporous sheet has been grafted with a poloxamer or a blend thereof. Still more preferably, the polyolefin of the hydrophilized microporous sheet has been grafted with a poloxamer having the following structure:

[0071] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0072] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90. Most preferably, the poloxamer is equivalent to that sold under the trade name PLURONIC TM A polymer sold as P-123 (Sigma-Aldrich).

[0073] Preferably, the polyolefin is selected from poly(ethylene), poly(propylene), poly(butylene) and poly(methylpentene). More preferably, the polyolefin is poly(ethylene) or poly(propylene). Most preferably, the polyolefin is poly(ethylene).

[0074] In a first embodiment of the third aspect, there is provided a composite membrane consisting essentially of a film of at least partially cross-linked poly(vinyl alcohol) adhered to a microporous sheet of polyolefin grafted with a poloxamer.

[0075] In a second embodiment of the third aspect, there is provided a composite membrane consisting essentially of a film of at least partially cross-linked poly(vinyl alcohol) adhered to a microporous sheet of poly(ethylene) grafted with a poloxamer, wherein the poloxamer is equivalent to that sold under the trade name PLURONIC TM A polymer sold as P-123 (Sigma-Aldrich).

[0076] Preferably, the composite membrane is an asymmetric composite membrane.

[0077] In a fourth aspect, a method for preparing a water wettable filter membrane is provided, wherein the method comprises:

[0078] 1. contacting a microporous sheet of polyolefin with a solution comprising poloxamer in a solvent to provide a contacted sheet;

[0079] 2. irradiating the contacted sheet with ultraviolet light in the presence of a photoinitiator to provide an irradiated sheet; and then

[0080] 3. Wash and dry the irradiated sheet to provide a film.

[0081] Preferably, the polyolefin is poly(ethylene) or poly(propylene). More preferably, the polyolefin is poly(ethylene). Most preferably, the polyolefin is unprocessed poly(ethylene).

[0082] Preferably, the solution comprises a photoinitiator. More preferably, the solution additionally comprises a cross-linking agent.

[0083] Preferably, the poloxamer is a polymer having the following structure:

[0084] HO(ethylene oxide) m -(Propylene oxide) n -(ethylene oxide) m H

[0085] wherein m is in the range of 15 to 25 and n is in the range of 50 to 90. Most preferably, the poloxamer is equivalent to that sold under the trade name PLURONIC TM P-123 (Sigma-Aldrich) is a triblock copolymer. It should be understood that for the triblock copolymers sold under the trade name PLURONIC TM A polymer sold as P-123 (Sigma-Aldrich) with m being 20 and n being 70.

[0086] Preferably, the solvent is water-alcohol or water-acetone, wherein the ratio of water to alcohol or acetone (v / v) is in the range of 1: 1 to 3: 1. More preferably, the ratio of water to alcohol or acetone (v / v) is in the range of 1: 1 to 2: 1. Most preferably, the solvent is water-ethanol.

[0087] Preferably, the photoinitiator is a Type II photoinitiator.Most preferably, the photoinitiator is benzophenone (benzophenone; BP).

[0088] Preferably, the crosslinking agent has a molecular weight of less than 150 g mol -1 Most preferably, the crosslinking agent is divinylbenzene (DVB).

[0089] Preferably, the ultraviolet light is UVC light. Preferably, the wavelength of the ultraviolet light is concentrated in the range of 250 to 360 nm. More preferably, the wavelength of the ultraviolet light is concentrated in the range of 250 to 280 nm. Most preferably, the wavelength of the ultraviolet light is concentrated at 250 nm.

[0090] Preferably, the irradiation lasts for a time between 1 and a half minutes and 2 and a half minutes. More preferably, the irradiation lasts for a time of 2 minutes plus or minus 10 seconds.

[0091] In one embodiment of the fourth aspect, there is provided a method of preparing a water wettable membrane, the method comprising irradiating a microporous sheet of poly(ethylene) with a wavelength centered at 250 nm, the microporous sheet of poly(ethylene) having been treated with 3 to 5% (w / v) of PLURONIC TM P-123 provides an impregnation of poloxamer, 0.5 to 1% (w / v) benzophenone, and 0 to 0.5% (w / v) divinylbenzene in a 30 to 50% (v / v) ethanol aqueous solution.

[0092] It is contemplated that poly(propylene) may replace poly(ethylene) in this embodiment of the fourth aspect.

[0093] In a fifth aspect, a method for preparing a composite membrane is provided, the method comprising:

[0094] 1. Contacting the following in the presence of a free radical initiator:

[0095] a solution of poly(vinyl alcohol) in a first solvent, and

[0096] The hydrophilized microporous sheet of the first or second aspect,

[0097] to provide a contacted sheet;

[0098] 2. irradiating the contacted sheet with ultraviolet light to provide an irradiated sheet;

[0099] 3. drying the irradiated sheet to provide a dried sheet; and then

[0100] 4. Washing the dried sheet in a second solvent to provide a composite membrane.

[0101] Preferably, the hydrophilized microporous sheet of the first or second aspect will be a hydrophilized microporous sheet of a polyolefin, wherein the polyolefin has been grafted with a poloxamer or a blend of preformed polymers comprising a poloxamer.

[0102] Preferably, the first solvent is water-ethanol or water.

[0103] Preferably, the second solvent is water.

[0104] Preferably, the contacted microporous sheet is dried by applying a positive thermal gradient across the thickness of the sheet from one side of the hydrophilized microporous sheet to the other side of the sheet.

[0105] Preferably, the composite membrane is an asymmetric composite membrane.

[0106] In a sixth aspect, there is provided a method of removing particles from an aqueous feed stream, the method comprising contacting a first side of a filter membrane of the first or second aspect with the feed stream at a pressure sufficient to provide permeation.

[0107] Preferably, the feed stream is selected from cleaning solutions and wastewater. More preferably, the feed stream is selected from alkaline cleaning solutions, citric acid cleaning solutions and hypochlorite cleaning solutions.

[0108] The particles may be microscopic in size. The particles may be of abiotic or biological origin, including bacterial cells. Preferably, the pressure is less than 10 bar. Preferably, the filter membrane is in the form of a spirally wound filter membrane assembly or filter element.

[0109] In a seventh aspect, the present invention provides a spirally wound filtration membrane module or filter element comprising the membrane of the first, second or third aspect.

[0110] In the description and claims of this specification, the following abbreviations, acronyms, phrases and terms have the meanings provided: "block" refers to a portion of a macromolecule comprising a number of building blocks having a composition or configuration feature not present in at least one adjacent portion; "CAS RN" refers to a Chemical Abstracts Service (CAS, Columbus, Ohio) registration number; "comprising" means "including," "containing," or "characterized by" and does not exclude any additional elements, ingredients, or steps; "consisting essentially of" means excluding any element, ingredient, or step without material limitation; "consisting of" means excluding any unspecified element, ingredient, or step other than impurities and other incidentals; "crosslinking" refers to a reaction involving sites or groups on an existing macromolecule or an interaction between existing macromolecules, which results in the formation of a small region in the macromolecule, such as a cross-linking bridge, from which at least four chains extend. "crosslinker" refers to a material that is incorporated into the crosslinks of a crosslinked polymer network; "curing" refers to the chemical process of converting a prepolymer or polymer into a polymer of higher molecular weight and connectivity and ultimately into a network; "filtration" refers to the removal of particles from a fluid by passage through a porous substrate, and "filtration" has a corresponding meaning; "flux" refers to the rate of permeate transported per unit membrane area (volume per unit time); "grafted polymer" refers to a polymer in which a linear backbone is attached at various points to side chains having a structure different from that of the backbone; "Grafting" refers to a reaction in which one or more types of blocks are attached to the main chain of a macromolecule through side chains having a different structural configuration characteristic from that in the main chain, and "grafted" has a corresponding meaning; "homopolymer" refers to a polymer formed by the polymerization of a single monomer; "hydrophilic" means having a tendency to mix with, dissolve in or be wetted by water, and "hydrophilicity", "hydrophilized" and "hydrophilicitizing" have a corresponding meaning; "LM H" means liters per square meter per hour; "impregnation" means, for example, penetration of a substrate with a solution of an agent in a solvent; "macromolecule" or "polymer" means a molecule of high relative molecular mass, the structure of which essentially comprises a plurality of repeating units, which are actually or conceptually derived from molecules of low relative molecular mass; "microporous" means a discontinuous matrix consisting of an essentially continuous matrix structure containing essentially uniform small pores or channels throughout the body of the substrate (such as can be produced using casting (wet) processing techniques) and specifically excluding woven or nonwoven fibers; "micro-sized" means having a size as low as 0.5 micrometers in size; "monomeric molecule" refers to a molecule that can undergo polymerization to provide a building block for the basic structure of a macromolecule; "monomeric unit", "monomeric unit" or "mer" refers to the largest building block of a macromolecular structure composed of a single monomer molecule; "partially cross-linked" means that only a portion of the sites available for cross-linking are utilized and the cross-linking reaction is limited by reagents, temperature or time period; "permeable" means allowing the passage of solvents such as water; "permeate" means diffusion in the bulk; "photoinitiator" refers to a photolabile compound that forms free radicals when irradiated; "poloxamer" refers to a symmetrical nonionic triblock copolymer consisting of a central chain of poly(propylene oxide) flanked by two chains of poly(ethylene oxide); "poly(vinyl alcohol)" and "polyvinyl alcohol" are used synonymously; "post-treated polymer" refers to a polymer that has been partially or completely modified after the basic polymer backbone has been formed; "preformed" refers to a polymer that has been pre-formed (i.e., pre-formed) "PSSS" or "pSSS" means the product of polymerization of SSS, i.e., poly(4-vinylbenzenesulfonic acid); "PVA" means poly(vinyl alcohol) (or polyvinyl alcohol); "semi-permeable" means allowing certain substances to pass through but not others, in particular allowing solvents such as water to pass through but not certain solutes such as proteins, salts or sugars to pass through; "SSS" means sodium styrene sulfonate, i.e., the sodium salt of 4-vinylbenzenesulfonic acid; "UVA" means electromagnetic radiation having a wavelength between 320 and 400 nm; "UVB" means electromagnetic radiation having a wavelength between 290 and 320 nm; "UVC" means electromagnetic radiation having a wavelength between 200 and 290 nm; "water-wettable" means wettable by water; "wettable" means becoming permeable with a solvent such as water when in contact with the solvent under standard laboratory conditions (i.e., 25°C, 100 kPa), and "xPVA" means at least partially cross-linked PVA. .

[0111] Synonyms for any defined terms have corresponding meanings. When there is uncertainty about the meaning of undefined abbreviations, acronyms, phrases or terms related to polymer terminology and nomenclature, the meaning provided in the publication of Jones et al. (2008) shall prevail. The terms "first", "second", "third", etc., used with reference to elements, features or the whole of the subject matter defined in the description or claims, or when used with reference to alternative embodiments of the present invention, are not intended to imply a preferred order. The text or numbering of the examples and comparative examples (if any) is not intended to indicate that any pair of examples and comparative examples are directly comparable. When values ​​are expressed as one or more decimal places, standard rounding is applied. For example, 1.7 includes a range of 1.650 cycles to 1.749 cycles. When the concentration or ratio of an agent or solvent is defined, the concentration or ratio defined is the initial concentration or ratio of the agent or solvent. Similarly, when the pH or pH range is defined, the pH or pH range defined is the initial pH or pH range. Reference to the use of 4-vinylbenzenesulfonic acid includes reference to the use of salts of the acid, including SSS. It will be appreciated that the porosity measured for a substrate will depend, at least in part, on the method used to determine the porosity. In this specification, the term "microporous" is used to refer to the porosity of a polyolefin sheet, which is equivalent to TARGRAY TM The porosity of wet-laid polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada). In this context, the term "equivalent" means that the porosity of the polyolefin sheet is determined by the same method as that of TARGRAY. TM Wet-laid polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada) had a porosity of 75 to 125%.

[0112] The present invention will now be described with reference to the embodiments or examples and the drawings of the accompanying drawings. In the brief description of the drawings and elsewhere in the following description, reference to the "top" (Ctop, Etop, etc.) of the membrane refers to the face or side of the membrane or sheet in contact with the working solution. Reference to the "back" (Cback, Eback, etc.) or "back layer" refers to the opposite face or side. It should be understood that since the membrane or sheet is installed in the filter membrane assembly, the entire face or side is not exposed to the feed flow. A description of the filter membrane assembly (Sterlitech Corp.) and its use is provided on page 24, line 24 in the specification of the accompanying international application number PCT / NZ2015 / 050034 [publication number WO 2015 / 147657A1]. BRIEF DESCRIPTION OF THE DRAWINGS

[0113] Figure 1 . Exploded view of the filter membrane assembly (Sterlitech Corp.) used in flux testing of sheet samples of filter membrane.

[0114] Figure 2 .Untreated microporous poly(ethylene) (TARGRAY TM Wet-processed polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada)) (raw PE), triblock copolymer (PLURONIC) used to prepare sample (P123) TM P-123; lot #MKCC2305, Sigma-Aldrich) and the spectra recorded on the top (Etop) and back (Eback) sides of each sample designated as 040918Wiv, 040918Wv, and 040918Wvi (3800 cm -1 Up to 525cm -1 ) comparison.

[0115] Figure 3 .In the "fingerprint area" (1800cm -1 Up to 600cm -1 ) Figure 2 Comparison of spectra.

[0116] Figure 4 Spectra recorded for the region of the sample designated 040918Wvi with or without exposure (Ctop and Cback) to the feed stream (3800 cm -1 Up to 525cm -1 ) comparison.

[0117] Figure 5 Scanning electron micrographs of the top (Etop) side of the sample designated 040918Wiv at 250,000x (A), 35,000x (B), and 10,000x (C) magnifications.

[0118] Figure 6 Scanning electron micrographs of two areas on the top (Etop) side of the sample designated 040918Wiv at a magnification of 10,000x.

[0119] Figure 7 . Comparison of the flux (LMH) maintained by filter membrane samples (180419Wi and 230419Wii (■); 180419Wii and 230419Wiii (●)) prepared with a cross-linking agent (DVB) (solid line) and without a cross-linking agent (DVB) (dashed line).

[0120] Figure 8 . Schematic diagram of a prototype production line for preparing a water-wettable filter membrane according to Example C.

[0121] Fig. 9 Photographs of bottles containing samples of spent alkaline cleaning solution (left bottle) and permeate after filtration of the spent alkaline cleaning solution as described in Example E (right bottle).

[0122] Fig.10 . Fig. 9 Plot of flow rate (liters / minute) versus time reading (seconds) at each of the two inlets for the rate (solid and dashed lines) during filtration of the spent alkaline cleaning solution shown in (left bottle).

[0123] Fig.11 . Fig. 9 Plot of the flow rate of permeate (liters / minute) versus the timer reading (seconds) during filtration of the spent alkaline cleaning solution shown in (right bottle).

[0124] Fig.12 Photographs of bottles containing samples of less pigmented less colored used alkaline cleaning solution (left bottle) and permeate after filtration of the used alkaline cleaning solution as described in Example E (right bottle).

[0125] Fig.13 . Fig.12 Plot of flow rate of permeate (liters / minute) versus timer reading (seconds) for filtration of spent alkaline cleaning solution showing less coloration shown in (right bottle).

[0126] Fig.14 Photographs of bottles containing samples of heavily contaminated (ie, high solids) spent alkaline cleaning solution (left and center bottles) and permeate after filtration of spent alkaline cleaning solution as described in Example E (right bottle).

[0127] Fig.15 Photographs of bottles containing samples of used citric acid cleaning solution (left bottle) and the permeate (middle bottle) and concentrate (ie, retentate) (right bottle) after filtration of the used citric acid cleaning solution.

[0128] Fig.16 . Fig.15 Plot of the flow rate of permeate (liters / minute) versus the time reading (seconds) during filtration of the spent citric acid rinse solution shown in (middle bottle).

[0129] Fig.17Appearance of 10 mL volumes of working solutions prepared according to Methods 1, 2, and 3 of Example G. "Working Solution A" contained 0.15 g poly(vinyl alcohol) (PVA, 65 kDa). "Working Solution B" contained 0.25 g poly(vinyl alcohol) (PVA, 65 kDa). The turbid "Working Solution C" contained 0.5 g poly(vinyl alcohol) (PVA, 65 kDa).

[0130] Fig.18 . Appearance of replicate samples prepared according to Method 6 of Example G and named 041918wi, 041918wii and 041918wiii.

[0131] Fig.19 .Untreated microporous poly(ethylene) (TARGRAY TM Wet-laid polyethylene separator, Cat. No. SW320H (Targray, Kirkland QC, Canada)) (raw PE), triblock copolymer for sample preparation (PLURONIC TM P-123; lot #MKCC2305, Sigma-Aldrich) (P123) and poly (vinyl alcohol) (PVA, 65 kDa) (PVA65), and the center (-C) and edge (-E) spectra recorded for each of the samples designated 310818wi, 030918wii and 030918wi (3800 cm -1 Up to 525cm -1 ) comparison.

[0132] Fig. 20 .Untreated microporous poly(ethylene) (TARGRAY TM Wet-processed polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada)) (raw PE), triblock copolymer used to prepare samples (PLURONIC TM P-123; lot #MKCC2305, Sigma-Aldrich) (P123) and poly(vinyl alcohol) (PVA, 65 kDa) (PVA65), as well as the center (-C) and edge (-E) of each of the samples designated 310818wi, 030918wii and 030918wi recorded in the “fingerprint region” (1800 cm -1 Up to 600cm -1 ) is compared with the enlarged spectra on .

[0133] Fig.21 Photographs of vials containing partially cross-linked poly(vinyl alcohol) (xPVA) prepared according to Method 2 of Example H. From left to right: Vial 1, Vial 2, Vial 3, and Vial 4. DETAILED DESCRIPTION

[0134] Filter membranes are used in a range of industrial processes including food processing to recycle or remove water from feed streams. In one application, the purpose may be to separate water from contaminant particles. In another application, the purpose may be to concentrate high-value solutes. In either application, efficiency is increased by contacting the feed stream with the large surface area of ​​the filter membrane. For this reason, filter membranes are typically assembled into spirally wound filter elements, which are then installed in industrial equipment. Such spirally wound membrane modules, or "filter elements," are provided by manufacturers such as Synder Filtration (Vacaville, California, USA).

[0135] Higher efficiencies can be achieved if cleaning can be performed in situ without the need to remove and reinstall the filter element. Cleaning in situ solutions use chemically aggressive solutions such as acids, bases, and hypochlorites. Alternatively, the feed stream to which the membrane is exposed may be chemically aggressive, and durability under these conditions reduces the frequency with which filter element replacement is required.

[0136] Microporous sheets of polyolefins such as poly(ethylene) are commercially available from suppliers such as Celgard (Charlotte, North Carolina, USA) and Targray (Kirkland, Quebec, Canada). One obstacle to using these substrates as filter membranes in the above applications is the inherent hydrophobicity. When the goal is to provide a semipermeable membrane for concentrating high-value solutes, it may also lack the desired retention characteristics.

[0137] It has now been determined that the grafting of microporous sheets of poly(ethylene) with preformed polymers such as poloxamers supplied under the trade name PLURONIC-P123 provides a filter membrane that is easily wetted with water and provides high flux rates at relatively low pressures (5 bar). The filter membranes so produced have also demonstrated the desired durability when exposed to chemically aggressive liquids. The retention of these desired properties is enhanced by the addition of a crosslinking agent in the working solution used in the preparation method - attributable to the grafting. Without wishing to be bound by theory, low molecular weight crosslinking agents are advantageous so as not to destroy the favorable retention properties also exhibited by the membrane.

[0138] The method for preparing the filter membrane is easily adaptable to a continuous production process. According to the described method, the microporous substrate is impregnated with a working solution of the following composition prior to irradiation with UV light having a wavelength in the range of 250 nm to 360 nm, preferably at or near the lower end of this range (250 nm).

[0139] Working solution:

[0140] 3 to 5% (w / v) poloxamer

[0141] 0.5 to 1% (w / v) photoinitiator

[0142] 0 to 0.5% (w / v) crosslinker

[0143] 30 to 50% (v / v) alcohol or acetone in water ('solvent')

[0144] A preferred poloxamer for use in the working solution is provided under the trade name PLURONIC P-123. A preferred photoinitiator for use in the working solution is benzophenone. A preferred crosslinker for use in the working solution is divinylbenzene.

[0145] The working solution may additionally comprise a second preformed polymer dispersed in a solvent. A suitable second preformed polymer is poly(ethanol). The inclusion of a second preformed polymer may be used to improve the properties (durability, flux or selectivity) of the filter membrane.

[0146] Example A - Preparation of filter membranes (laboratory method, poloxamer only)

[0147] A volume of 5 mL of 10% (w / v) triblock copolymer (PLURONIC TM P-123; lot#MKCC2305, Sigma-Aldrich) was mixed with an equal volume of deionized water. An amount of 0.1 g of the photoinitiator benzophenone (benzophenone; Ph2O) was dissolved in a separate volume of 5 mL of ethanol and then added to the diluted solution of the triblock copolymer. The working solution was stored in the dark until use.

[0148] From microporous poly(ethylene) sheets (TARGRAY TM Samples (13.5 x 18.5 cm) were cut from wet-laid polyethylene separators, Catalog No. SW320H (Targray, Kirkland QC, Canada), and each sample was coated with a volume of 5 mL of the working solution. The coated samples were then irradiated with ultraviolet (UV) light in the range of 250 to 360 nm for 2 minutes, then rinsed with water and air dried on top of a warm oven.

[0149] Four replicate samples prepared according to this method were named 040918Wiv, 040918Wv, 040918Wvi and 151018Wi. A small piece of the sample named 040918Wiv was cut from the edge of the sample and subjected to scanning electron microscopy (SEM).

[0150] Each sample was readily wetted with water and was observed to become uniformly transparent when in contact with the solvent.

[0151] Durability, flux, and protein retention

[0152] Use as Figure 1 The flux (LMH) of each sample named 040918Wiv, 040918Wv and 040918Wvi was determined using the filter membrane assembly (Sterlitech) shown in Figure 1. The samples were individually installed in the filter membrane assembly and the flux was measured at 0 and 5 bar. The time to collect a predetermined volume of permeate at a specified pressure and temperature was recorded and the flux (J) was calculated according to the following equation:

[0153]

[0154] where V is the volume of permeate (L), t is the time (h) for which V is collected, and A is the area (m2) of the sample exposed to the feed stream (water or skim milk). 2 The results are summarized in

[0155] Table 1.

[0156]

[0157] Table 1. Fluxes (LMH) measured at 0 and 5 bar with water as feed stream at the indicated temperatures (°C).

[0158] To assess durability, flux was also measured after repeated cleaning-in-place (CIP) protocols. The CIP protocol was based on protocols employed in commercial process operations for reverse osmosis (RO) membranes (Anon (2014)) and is summarized in Table 2.

[0159] step Feed Flow Time (minutes) Temperature(℃) 1 water 5 Ambient temperature 2 water 5 35 3 Alkali 5 35 4 water 5 35 5 acid 10 35 6 water 5 Ambient temperature 7 Hypochlorite 5 35 8 water 5 Ambient temperature

[0160] Table 2. Cleaning-in-place (CIP) protocol adapted from Anon (2014). "Base" is 2% (w / v) sodium hydroxide (NaOH). "Acid" is 1.9% (w / v) nitric acid (H2NO3) and 0.6 (w / v) phosphoric acid (H3PO4).

[0161] For each sample, multiple CIP protocols were repeated using either water or skim milk as the feed stream in alternation. The flux and protein retention percentages determined for the samples designated 040918Wv and 040918Wvi (with skim milk as the feed stream) are provided in Table 3. The total protein concentration in the permeate was calculated based on HPLC analysis monitored by UV absorbance.

[0162]

[0163]

[0164] Table 3. Flux (LMH) and protein retention measured at 0 and 5 bar with water or skim milk as feed stream at the indicated temperature (°C). Each sample was measured following a repeated cleaning-in-place (CIP) protocol.

[0165] The durability of the filter membrane was further evaluated by contacting the sample designated 151018Wi with 2% (w / v) sodium hydroxide (NaOH) for 7 days. The flux and protein retention percentage measured for these samples (using skim milk as the feed stream) are provided in Table 4.

[0166]

[0167] Table 4. Flux (LMH) and protein retention measured at the indicated temperatures (°C) at 0 and 5 bar with water or skim milk as feed stream. The samples were measured after 7 days exposure to 2% (w / v) sodium hydroxide (NaOH).

[0168] Fourier transform infrared (FTIR) spectroscopy

[0169] The spectra of each sample, designated 040918Wiv, 040918Wv and 040918Wvi, were recorded using a Thermo Electron Nicolet 8700 FTIR spectrometer equipped with a single reflection ATR and a diamond crystal. -1 32 scans with a resolution of 1000 nm were averaged. Figure 2 The recorded spectrum (3800 cm -1 Up to 525cm -1 ) are compared with: (i) untreated microporous poly (ethylene) (TARGRAY TM Wet-laid polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada)) ('raw PE'); (ii) triblock copolymer (PLURONIC TM P-123; lot #MKCC2305, Sigma-Aldrich) ('P123'); and (iii) the top (Etop) and back (Eback) sides of each sample designated 040918Wiv, 040918Wv, and 040918Wvi.

[0170] Corresponding to the presence of triblock copolymers (PLURONIC TM The COC fragment (1108 cm -1 ) and the symmetric stretching mode of CH3 (2970cm -1) are also present in the spectra recorded for each sample. TM Many of the signal characteristics of P-123 are also Figure 3 The triblock copolymer (PLURONIC TM The signal characteristic of P-123) is retained in the spectrum recorded for the region of the sample designated 040918Wiv after exposure to the feed stream (water), as shown in Figure 4 shown.

[0171] SEM

[0172] Figure 5 and Figure 6 A scanning electron micrograph of a small piece cut from the edge of a sample designated 040918Wiv is provided in. The poly(ethylene) fibers of the microporous sheet appear to be coated.

[0173] FTIR spectroscopy and SEM observations appear to confirm the grafting of the poloxamer onto the polyolefin matrix of the microporous sheet. The conversion of the inherently hydrophobic microporous sheet of polyolefin into a water wettable and permeable membrane is attributed to this grafting.

[0174] Example B - Preparation of filter membrane (laboratory method)

[0175] A volume of 10 mL of 10% (w / v) triblock copolymer (PLURONIC TM P-123; lot#MKCC2305, Sigma-Aldrich) was mixed with an equal volume of deionized water. An amount of 0.2 g of the photoinitiator benzophenone (dibenzophenone; Ph2O) and 0 or 0.1 g of the crosslinker divinylbenzene (DVB) were dissolved in a separate volume of 10 mL of ethanol (methylated spirit) and then added to a volume of 10 mL of the diluted solution of the triblock copolymer. These working solutions—without or with the crosslinker DVB—were stored in the dark until use.

[0176] From microporous poly(ethylene) sheets (TARGRAY TM Samples (13.5 x 18.5 cm) were cut from a wet-laid polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada), and each sample was coated with a certain volume of one of the working solutions. The coated samples were then irradiated with ultraviolet (UV) light in the range of 250 to 360 nm for 2 minutes, then rinsed with water and air-dried in open air.

[0177] Three replicates prepared according to this method using a working solution that did not include DVB were named 110419Wi, 180419Wi, and 180419Wii. Three replicates prepared according to this method using a working solution that included DVB were named 230419Wi, 230419Wii, and 230419Wiii. Each sample was easily wetted with water, and each sample was observed to become uniformly transparent when in contact with the solvent.

[0178] The water flux of each sample was measured with deionized water as the feed stream (DI1). The samples were then completely dried and the water flux was measured again with deionized water as the feed stream (DI2). Each sample was then subjected to a clean-in-place (CIP) protocol and the water flux was then measured with deionized water as the feed stream (DI3 and DI4) and the samples were dried two more times. Each sample remained easily wetted with water. The results are summarized in Tables 5 and 6 and are shown in Table 6. Figure 7 for comparison.

[0179]

[0180] Table 5. Average fluxes (LMH) measured at room temperature (22 to 24°C) at 0 and 5 bar with water as feed flow (* membrane failure). No cross-linker was included in the 'working solution'.

[0181]

[0182] Table 6. Average fluxes (LMH) measured at room temperature (22 to 24°C) at 0 and 5 bar with water as feed flow. The crosslinker (DVB) was included in the "working solution".

[0183] Example C - Preparation of filter membrane (prototype method)

[0184] A volume of 300 mL of 10% (w / v) triblock copolymer (PLURONIC TM P-123; lot#MKCC2305, Sigma-Aldrich) in distilled water was dispensed into a reservoir protected from exposure to light. An additional 300 mL volume of distilled water was then added to provide 5% (w / v) triblock copolymer (PLURONIC TM P-123; lot#MKCC2305, Sigma-Aldrich). A 1.5% (w / v) solution of benzophenone in ethanol (methylated spirits) was prepared separately, and a volume of the crosslinker divinylbenzene (DVB) was added to provide a final concentration of 0.75% (v / v) DVB. A volume of 400 mL of this separately prepared solution was then mixed with a triblock copolymer (PLURONIC TMP-123; lot #MKCC2305, Sigma-Aldrich) were mixed in the reservoir to provide the working solution.

[0185] Refer to the attached page Figure 8 Peristaltic pumps (1, 2) are used to deliver the working solution from the reservoir (3, 4) to the two semi-cylindrical tanks (5, 6) of the prototype production line. During operation of the prototype production line, the reservoir is regularly replenished with working solution.

[0186] A continuous microporous sheet (7) of microporous poly(ethylene) is fed in width from a feed distribution roll to a first impregnation station comprising an idler roller (8) coaxially mounted in the first of two semi-cylindrical troughs (5). The difference between the radius of the roller (8) and the trough (5) is sufficient to allow the sheet (7) to pass freely around the roller and through the trough, but not so great as to promote evaporation of the working solution in the trough. The surface of the roller (8) over which the sheet (7) passes may be spirally engraved to promote the passage of the working solution across the length of the surface.

[0187] The sheet (7) leaving the first impregnation station is then fed vertically to a first irradiation station comprising a slotted chamber (9) containing two opposing arrays (10, 11) of UV light sources. The sheet (7) passes between the opposing arrays (10, 11) so that both sides are irradiated. The feed rate of the sheet (7) is adjusted to provide the required residence time in the slotted chamber (9).

[0188] The irradiated sheet (7) is then passed through a second dipping station (12) and a second irradiation station (13) having the same configuration as the first dipping station and the first irradiation station. After these repeated steps, the irradiated sheet (7) is fed in a washing station (17) around a plurality of idler rollers (14, 15, 16) immersed in water. The water in the washing station (17) is circulated by an external pump (18), and the depth of the water is controlled by a combination of a level transmitter and a solenoid valve (19). The combination of the plurality of idler rollers (14, 15, 16) and the water depth ensures sufficient residence time of the washed sheet (7) before it is fed into the drying station.

[0189] The drying station is a forced air dryer comprising two plenum chambers (20, 21) with opposed perforated panels between which the substrate sheet passes. A hot air blower (22, 23) mounted in the wall of each chamber forces air through the perforated panels. The dried substrate sheet (7) is then rewound onto a take-up roll (not shown).

[0190] Example D - Spiral Wound Filter Element, Housing and Frame

[0191] Spirally wound filter elements were made using filter membranes prepared according to the prototype method (Example C). The filter elements were wound using a Type 34 diamond pad. Two spirally wound filter elements were mounted in series in each of two housings mounted in an assembly ('frame').

[0192] Example E - Recovery of Cleaning Solution

[0193] The alkaline cleaning solution used to disinfect the wine tanks was collected in a volume of 900 liters and transferred to the rack reservoir in two volumes of 300 liters and 600 liters respectively and delivered to the inlet port of the filter housing by a circulation pump. The used alkaline solution has a translucent appearance caused by the suspension of particles ( Fig. 9 , left). The solution is pumped from the reservoir to the rack at a constant pressure to provide a flow rate of 110 to 120 liters per minute at the filter housing inlet ( Fig.10 Permeate was collected from each filter housing outlet at an initial rate of approximately 9 liters per minute, decreasing to a steady rate of approximately 5.8 liters per minute during pump operation ( Fig.11 The observed flux drop was attributed to concentration of the retentate in the closed system (rather than fouling of the membrane or separators). This attribution is supported by the near-constant flow rate observed at the housing inlet.

[0194] A volume concentration factor (VCF) of 8.18 was achieved within an initial duration of 2.5 hours (including a 20 minute downtime during which the contents of the reservoir were replenished), which corresponds to 88% recovery of the alkaline cleaning solution.

[0195] The contents of the reservoir were replenished with an additional volume of 600 liters of the alkaline cleaning solution that had been used to sanitize the wine tanks but contained less pigment ( Fig.12 , left), and repeat the previous steps to increase the volume concentration factor to 15. Using this second feed material ( Fig.13 ) An increase in the permeate flux rate was observed, which supports that minimal fouling of the membrane and separator occurred during the initial run.

[0196] The contents of the reservoir were replenished with an additional volume of 500 liters of alkaline cleaning solution that had been used to sanitize wine tanks but was heavily contaminated with solids ( Fig.14 , left), a final volume concentration factor of 20 was achieved, albeit with a reduction in permeate flux of approximately 3 liters per minute. A volume concentration factor of 20 corresponds to a recovery of 95% (w / w) of the alkaline cleaning solution.

[0197] Cumulative volumes (900 L, 1,500 L, and 2,000 L) of samples of the recovered alkaline cleaning solution were titrated to pH 7 using 0.1 N sulfuric acid (H2SO4) and an automatic titrator.

[0198]

[0199] Table 7. Recovery of alkaline cleaning solutions from a series of cleaning operations. (*Dilution of feed stream during process)

[0200] To demonstrate the membrane's durability against multiple chemicals and its usefulness for recovery and reuse of cleaning solutions commonly used in beverage and food processing, a volume of citric acid cleaning solution ( Fig.15 , left). This volume was transferred to a clean reservoir and pumped to the filter housing inlet at a similar flow rate. An average permeate flow rate of approximately 4 liters per minute was obtained during the run ( Fig.16 ). Greater than 95% (w / w) of the citric acid cleaning solution was recovered.

[0201] Example F - Reuse of Cleaning Solution

[0202] The recovered cleaning solution was used to sanitize wine tanks and evaluate the effectiveness of these steps. The cleaning solution can be repeatedly recovered and reused to demonstrate the commercial viability of the process. In addition to the evaluation of the effectiveness of the sanitization operation, the content of the recovered and reused cleaning solution was determined by titration as described above (Tables 8 and 9).

[0203]

[0204] Table 8. Recovery and reuse of alkaline cleaning solutions.

[0205]

[0206] Table 9. Recovery and reuse of citric acid cleaning solution.

[0207] Example G - Preparation of Filter Membranes (Laboratory Method, Polymer Blends)

[0208] Method 1

[0209] A volume of 5 mL of 10% (w / v) triblock copolymer (PLURONIC TM P-123; lot#MKCC2305, Sigma-Aldrich) in water was mixed with an equal volume of 0.25 g of poly(vinyl alcohol) (PVA, 65 kDa) in water. An amount of 0.1 g of the photoinitiator benzophenone (benzophenone; Ph2O) was dissolved in a separate volume of 5 mL of ethanol and then added to the diluted solution of the triblock copolymer and poly(vinyl alcohol) (PVA, 65 kDa). The solution ("Working Solution A") was stored in the dark until use.

[0210] Method 2

[0211] A volume of 5 mL of 10% (w / v) triblock copolymer (PLURONIC TM P-123; lot#MKCC2305, Sigma-Aldrich) was mixed with a 3 mL volume of 0.15 g aqueous solution of poly(vinyl alcohol) (PVA, 65 kDa). An amount of 0.1 g of the photoinitiator benzophenone (benzophenone; Ph2O) was dissolved in a separate volume of 5 mL of ethanol and then added to the diluted solution of the triblock copolymer and poly(vinyl alcohol) (PVA, 65 kDa). The solution ("Working Solution B") was stored in the dark until use.

[0212] Method 3

[0213] At 55°C, 0.5 g of a triblock copolymer (PLURONIC TM P-123; lot#MKCC2305, Sigma-Aldrich) was dissolved in a volume of 10 mL of 0.5 g of poly(vinyl alcohol) (PVA, 65 kDa) and a volume of 5 mL of ethanol was added to the aqueous solution. An amount of 0.1 g of the photoinitiator benzophenone (benzophenone; Ph2O) was dissolved in the solution of the triblock copolymer and poly(vinyl alcohol) (PVA, 65 kDa), and this turbid but homogeneous solution ("Working Solution C") was stored in the dark until use.

[0214] The appearance of each of the working solutions (A, B and C) prepared according to methods 1, 2 and 3 is as follows Fig.17 shown.

[0215] Method 4

[0216] From microporous poly(ethylene) sheets (TARGRAY TM Samples (13.5×18.5 cm) were cut from a wet polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada), and each sample was coated with a 5 mL volume of working solution. The coated samples were then irradiated with ultraviolet (UV) light in the range of 250 to 360 nm for 2 minutes, then rinsed with water and air-dried on top of a warm oven. Working solution A was used to prepare the sample named 310818wi, working solution B was used to prepare the sample named 030918wii, and working solution C was used to prepare the sample named 030918wi.

[0217] Each of the samples prepared according to Method 4 was highly hydrophilic and easily wetted by water.

[0218] Method 5

[0219] 0.15 g of poly(vinyl alcohol) (PVA, 146 to 186 kDa) was dissolved in a volume of 10 mL of water with heating and stirring. Then 0.5 g of the triblock copolymer (PLURONIC TM P-123; lot #MKCC2305, Sigma-Aldrich) was added to the volume and dissolved. An amount of 0.1 g of the photoinitiator benzophenone (benzophenone; Ph2O) was dissolved in a separate volume of 5 mL of ethanol and then added to the volume of the triblock copolymer and poly (vinyl alcohol) (PVA, 146 to 186 kDa) (PVA180). The solution ("Working Solution D") was stored in the dark until use.

[0220] Method 6

[0221] From microporous poly(ethylene) sheets (TARGRAY TM Samples (13.5 x 18.5 cm) were cut from wet-laid polyethylene separators, Catalog No. SW320H (Targray, Kirkland QC, Canada) and coated with a 5 mL volume of Working Solution D. The coated samples were then irradiated with ultraviolet (UV) light in the range of 250 to 360 nm for 2 minutes, then rinsed with water and air dried on top of a warm oven.

[0222] Three replicate samples were prepared according to Method 5 and named 041918wi, 041918wii and 041918wiii. The appearance of these samples is provided in Figure 8 middle.

[0223] The flux (LMH) was determined for each of the samples designated 310818wi, 030918wii and 030918wi. A summary of the composition of the working solution used to prepare each sample of the membrane and the flux determined is shown in Table 10.

[0224]

[0225] Table 10. Summary of the composition (g / 10 mL) of each working solution for each sample (310818wi, 030918wii, 030918wi and 040918wi) used to prepare the membranes and the flux (LMH) measured at 0 bar and 5 bar with water as feed stream.

[0226] For each sample designated 310818wi, 030918wii and 030918wi, the untreated microporous poly(ethylene) (TARGRAY TMWet-laid polyethylene separator, Catalog No. SW320H (Targray, Kirkland QC, Canada) and triblock copolymer (PLURONIC TM P-123; lot #MKCC2305, Sigma-Aldrich) and poly(vinyl alcohol) (PVA, 65 kDa). Spectra were recorded for the center (-C) and edge (-E) of each sample designated 310818wi, 030918wii and 030918wi. Comparison of the recorded spectra is provided in Fig.19 In the “fingerprint area” (1800cm -1 Up to 600cm -1 ) is provided in Fig. 20 (The edge of each sample was not exposed to the feed stream (water) during the flux test)

[0227] Example H - Preparation of composite membranes

[0228] Method 1

[0229] A series of preliminary experiments were conducted to evaluate the method of preparing a film of cross-linked poly(vinyl alcohol) (xPVA) on a surface. A solution of a free radical initiator sodium persulfate (SPS) was prepared by adding 0.2 g of SPS to a volume consisting of 10 mL of deionized water and 10 mL of acetone. The solution of the free radical initiator was applied to the surface of each of three glass plates (plate 1, plate 2, and plate 3). Plate 2 and plate 3 were transferred to an oven and dried at a temperature of 60°C until all solvents had evaporated to leave a thin initiator layer deposited on the surface. A poly(vinyl alcohol) (PVA) solution with a concentration of 1% (w / v) was prepared in dimethyl sulfoxide (DMSO) or deionized water. The poly(vinyl alcohol) (PVA) solution in DMSO was sprayed on the wet surface of plate 1, and the plate was then transferred to an oven and dried at a temperature of 60°C. The poly(vinyl alcohol) (PVA) solution in DMSO was also sprayed on the dry surface of plate 2, and the plate was then transferred to an oven and dried at a temperature of 60°C. A solution of poly(vinyl alcohol) (PVA) in deionized water was sprayed on the dry surface of Plate 3, and the plate was then transferred to an oven and dried at 60°C. No desired film of cross-linked poly(vinyl alcohol) was formed on Plate 1. The failure was due to the presence of acetone causing the polymer to precipitate out of the solution. The film formed on Plate 2 was too fragile to be used as a retention layer for a composite membrane. A transparent, peelable film was formed on the surface of Plate 3. The film was not brittle, and this preparation method is suitable for preparing composite membranes.

[0230] Method 2

[0231] A series of preliminary experiments were conducted to evaluate the method of preparing a membrane of partially cross-linked poly(vinyl alcohol) (xPVA), and thereby control the performance of the rejection layer of the composite membrane. A volume of 10 mL of a 1% (w / v) poly(vinyl alcohol) (PVA) solution in deionized water containing 0.1 g of SPS was dispensed into each of four vials (vial 1, vial 2, vial 3, and vial 4). The solution in each vial was heated to 75°C and maintained at that temperature with stirring until the following results were observed (the vials were then cooled):

[0232] Yellow solid precipitated out of solution (vial 1; 3 to 4 minutes)

[0233] A cloudy white solution with some precipitate formed (vial 2; approximately 3 minutes)

[0234] A cloudy white solution formed (vial 3; 1.5 to 2 minutes)

[0235] Turbid solution begins to form (vial 4; 10 to 20 minutes)

[0236] Observation results such as Fig.21 The partially cross-linked poly(vinyl alcohol) prepared according to the method described in vial 3 is suitable for the preparation of the membrane.

[0237] Method 3

[0238] In the proposed alternative method, a solution of the free radical initiator sodium persulfate (SPS) with a volume of 20 mL is prepared according to Method 1. A certain volume of a solution of partially cross-linked poly(vinyl alcohol) (xPVA) is prepared according to Method 2 (vial 3). The solution of the free radical initiator is applied to one surface of the hydrophilized microporous poly(vinyl alcohol) sheet prepared according to Example A. The sheet is then placed on a glass plate and transferred to an oven and dried at a temperature of 60°C. The partially cross-linked poly(vinyl alcohol) solution is applied to the same surface of the dried sheet, which is then returned to the oven and dried at a temperature of 60°C. The dried membrane is then rinsed with cold water and air-dried, and the flux, total solids and salt retention for different feed streams (water and milk) are then evaluated.

[0239] Method 4

[0240] A free radical initiator containing a volume of 8% (w / v) poly(vinyl alcohol) (PVA) was prepared by dissolving a 0.2 g amount of free radical initiator sodium persulfate (SPS) in 6.5 mL of deionized water, and then adding the solution to a volume of 13.5 mL of 12% (w / v) poly(vinyl alcohol) (PVA). The volume of 8% (w / v) poly(vinyl alcohol) (PVA) was stirred, heated to 75°C, and monitored until the solution turned pale yellow. The pale yellow solution was cooled and then applied to a hydrophilized microporous poly(vinyl alcohol) sheet prepared according to Example A. The sheet was then irradiated with ultraviolet (UV) light (250 nm) for 2 minutes and then dried on a glass plate in an oven at 60°C.

[0241] Method 5

[0242] A free radical initiator containing a volume of 5% (w / v) poly(vinyl alcohol) (PVA) was prepared by dissolving a 0.2 g amount of free radical initiator sodium persulfate (SPS) in 11.5 mL of deionized water, and then adding the solution to a volume of 8.5 mL of 12% (w / v) poly(vinyl alcohol) (PVA). The volume of 5% (w / v) poly(vinyl alcohol) (PVA) was stirred, heated to 75°C, and monitored until the solution turned pale yellow. The pale yellow solution was cooled and then applied to a hydrophilized microporous poly(vinyl alcohol) sheet prepared according to Example A. The sheet was then irradiated with ultraviolet (UV) light (250 nm) for 2 minutes and then dried on a glass plate in an oven at 60°C.

[0243] Samples of membranes prepared according to Method 4 and Method 5 were evaluated. Samples prepared according to Method 4 were also evaluated after exposure to a clean-in-place (CIP) protocol. The results of these evaluations are summarized in Table 11.

[0244]

[0245]

[0246] Table 11. Average flux (LMH) determined for water as feed stream and protein retention (%) and average flux (LMH) determined for milk as feed stream for samples of membranes prepared according to a particular method. Both feed streams were at a pressure of 5 bar. (* after exposure to a clean-in-place (CIP) protocol)

[0247] To manufacture composite membranes on an industrial scale, it is suggested to prepare a free radical initiator, such as sodium persulfate (SPS), containing 6 to 10% (w / v) poly(vinyl) (PVA) solution and apply it directly to the hydrophilized microporous polyolefin sheet, followed by irradiation with ultraviolet (UV) light and drying.

[0248] Although the present invention has been described with reference to embodiments or examples, it should be understood that, without departing from the scope of the present invention, these embodiments or examples can be changed and modified. In the case of having a specific element, feature or overall known equivalent, such equivalent is incorporated, as specifically mentioned in this specification. Unless otherwise specified, otherwise included in the variation and modification of the element, feature or overall embodiment or embodiment disclosed in the cited publication and selected from the cited publication all fall within the scope of the present invention. The advantages provided by the present invention and discussed in the specification can be provided in these different embodiments of the present invention in an optional manner or in combination.

[0249] Industrial Applicability

[0250] Methods of making membranes and their use in recovering aqueous solutions or water from feed streams are provided. The membranes are advantageously used where the membranes need to be exposed to chemically aggressive feed streams such as those used in clean-in-place operations in the beverage and food processing industries.

[0251] Incorporated by Reference

[0252] In the event that all or part of the claims, description or drawings of the present description are missing, the present description shall be completed by reference to the corresponding parts of the description attached to the most recently filed application claiming priority, in accordance with Rules 4.18, 20.5 and 20.6 of the PCT Regulations (in force from July 1, 2015 or as subsequently amended).

[0253] The disclosures of the following publications (more particularly identified in the "References" section below) are incorporated herein by reference in accordance with the provisions of 37 C.FR 1.57: Jones et al. (2008) and Schmolka (1973).

[0254] References

[0255] Allmer et al. (1988) Surface modification of polymers. I. Vapor-phase photografting with acrylic acid Journal of Polymer Science, Part A: Polymer Chemistry, 26(8), 2099-111.

[0256] Allmer et al. (1989) Surface modification of polymers. II. Grafting with glycidyl acrylates and the reactions of the grafted surfaces with amines Journal of Polymer Science: Part A: Polymer Chemistry, 27, 1641 - 1652.

[0257] Ang et al. (1980) Photosensitized grafting of styrene, 4 - vinylpyridine and methyl methacrylate to polypropylene Journal of Polymer Science: Polymer Letters Edition, 18, 471 - 475.

[0258] Anon (2014) DOW FILMTEC TM Membranes–Cleaning procedures for DOW FILMTEC FT30 elements Tech Fact(Form No.609 - 23010 - 0211).

[0259] Bai et al. (2011) Surface UV photografting of acrylic acid onto LDPE powder and its adhesion Shenyang Huagong Daxue Xuebao 25(2), 121 - 125.

[0260] Bolto et al. (2009) Crosslinked poly(vinyl alcohol) membranes Progress in Polymer Science, 34, 969 - 981.

[0261] Cadotte (1990) Alkali resistant hyperfiltration membrane United States patent no.4,895,661.

[0262] Carter et al. (2018) Controlling external versus internal pore modification of ultrafiltration membranes using surface-initiated AGET-ATRP Journal of Membrane Science, 554, 109-116.

[0263] Cheng et al. (2017) Method for preparing mesoporous composite film

[0264] Chinese patent application no. 201611226194 [Publ. no. CN 106731886 A].

[0265] Choi (2002) Graft polymerisation, separators, and batteries including the separators United States patent no. 6,384,100.

[0266] Choi (2004) Battery separator United States patent no. 6,680,144.

[0267] Choi (2005) Graft polymerisation, separators, and batteries including the separators United States patent no. 6,955,865.

[0268] Craft et al. (2017) Asymmetric composite membrane and a method of preparation thereof International application no. PCT / IB2016 / 055899 [publ. no. WO2017 / 056074A1].

[0269] Edge et al. (1993) Surface modification of polyethylene by photochemical grafting with 2-hydroxyethylmethacrylate Journal of Applied Polymer Science, 47, 1075-1082.

[0270] El Kholdi et al. (2004) Modification of adhesive properties of a polyethylene film by phtografting Journal of Applied Polymer Science 92(5), 2803-2811.

[0271] Exley (2016) Asymmetric composite membranes and modified substrates used in their preparation International application no. PCT / IB2015 / 060001 [Publication number WO 2016 / 103239 A1].

[0272] Gao et al. (2013) Radiation cross-linked lithium-ion battery separator with high rupture temperature and high tensile strength and manufacture method Chinese patent application no. 2013-10196439 (Publication number CN 103421208).

[0273] Guo et al. (2015) Coated microporous materials having filtration and adsorption properties and their use in fluid purification processes International application no. PCT / US2014 / 061326 [Publication number WO 2015 / 073161 A1].

[0274] Jaber and Gjoka (2016) Grafted ultra high molecular weight polyethylene microporous membranes international application no. PCT / US2015 / 061591 [Publication number WO2016 / 081729 A1].

[0275] Jones et al. (2008) Compendium of polymer terminology and nomenclature IUPAC Recommendations, RSC Publishing.

[0276] Kubota and Hata (1990a) Distribution of methacrylic acid-grafted chains introduced into polyethylene film by photografting Journal of Applied Polymer Science, 41, 689-695.

[0277] Kubota and Hata (1990b) Benzil-sensitized photografting of methacrylic acid on low-density polyethylene film Journal of Applied Polymer Science, 40, 1071-1075.

[0278] Linder et al. (1988) Semipermeable composite membranes, their manufacture and use United States patent no. 4,753,725.

[0279] Liu et al. (2014) With multi-scale gradient microstructure surface preparation method of a microporous membrane Chinese patent application no. 201310479920 [Publication number CN 103611437 A].

[0280] Ogiwara et al. (1981) Photosensitized grafting on polyolefin films in vapor and liquid phases Journal of Polymer Science: Polymer Letters Edition, 19, 457-462.

[0281] Schmolka (1973) Polyoxyethylene - polyoxypropylene aqueous gels United States patent no. 3,740,421.

[0282] Shentu et al. (2002) Factors affecting photo - grafting on low density polyethylene Hecheng Suzhi Ji Suliao 19(3), 5-8.

[0283] Singleton et al. (1993) Polymeric sheet International Application No. PCT / GB92 / 01245 (publication number WO 93 / 01622).

[0284] Tazuke and Kimura (1978) Surface photografting. I. Graft polymerization of hydrophilic monomers onto various polymer films Journal of Polymer Science: Polymer Letters Edition, 16, 497-500.

[0285] Wang et al. (2006) Pluronic polymers and polyethersulfone blend membranes with improved fouling - resistant ability and ultrafiltration performance Journal of Membrane Science, 283, 440-447.

[0286] Xu and Yang (2000) Study on the mechanism of LDPE-AA vapor-phase photografting system Gaofenzi Xuebao (2000), 5, 594-598.

[0287] Yang and Ranby (1996a) The role of far UV radiation in the photografting process Polymer Bulletin (Berlin), 37(1), 89-96.

[0288] Yang and Ranby (1996b) Bulk surface photografting process and its applications. II. Principal factors affecting surface photografting Journal of Applied Polymer Science, 63(3), 545-555.

[0289] Yang et al. (2014) Preparation and application of PVDF-HFP composite polymer electrolytes in LiNi 0.5 Co 0.2 Mn 0.3 O2 lithium-polymer batteries Electrochimica Acta 134, 258-265.

[0290] Yao and Ranby (1990a) Surface modification by continuous graft copolymerization. I. Photoinitiated graft copolymerization onto polyethylene tape film surface Journal of Applied Polymer Science, 40, 1647-1661.

[0291] Yao and Ranby (1990b) Surface modification by continuous graft copolymerization. III. Photoinitiated graft copolymerization onto poly(ethylene terephthalate) fiber surface Journal of Applied Polymer Science, 41, 1459 - 1467.

[0292] Yao and Ranby (1990c) Surface modification by continuous graft copolymerization. IV. Photoinitiated graft copolymerization onto polypropylene fiber surface Journal of Applied Polymer Science, 41, 1469 - 1478.

[0293] Zhang and Ranby (1991) Surface modification by continuous graft copolymerisation. II. Photoinitiated graft copolymerization onto polypropylene film surface Journal of Applied Polymer Science, 43, 621 - 636.

Claims

1. A water-wettable filter membrane comprising a microporous sheet of grafted polyolefin, wherein the polyolefin comprises a structure of HO(C2H4O) m -(C3H6O) n -(C2H4O) m A mixture of preformed polymers of poloxamers H, wherein m is in the range of 15 to 25 and n is in the range of 50 to 90, is grafted.

2. The water-wettable filter membrane of claim 1, wherein the preformed polymer mixture comprises polyvinyl alcohol.

3. The water-wettable filter membrane according to claim 1 or 2, wherein the polyolefin is polyethylene.

4. The water-wettable filter membrane according to claim 1 or 2, wherein m is 20 and n is 70.

5. The water-wettable filter membrane according to claim 1 or 2, wherein the graft comprises a cross-linking agent.

6. The water-wettable filter membrane according to claim 5, wherein the crosslinking agent has a molecular weight of less than 150 g mol -1 Molecular weight.

7. The water-wettable filter membrane according to claim 6, wherein the cross-linking agent is divinylbenzene.

8. A spirally wound filter element comprising the water-wettable filter membrane according to any one of claims 1 to 7.

9. A method for preparing a water-wettable filter membrane, comprising irradiating a polyethylene microporous sheet with UVC light, the polyethylene microporous sheet having been impregnated with a 30-50% (v / v) ethanol aqueous solution comprising a mixture of a preformed polymer containing 3 to 5% (w / v) poloxamer, 0.5 to 1% (w / v) benzophenone and 0 to 0.5% (w / v) divinylbenzene, wherein the poloxamer structure is HO(C2H4O) 20 -(C3H6O) 70 -(C2H4O) 20 H.

10. The method of claim 9, wherein the preformed polymer mixture comprises polyvinyl alcohol.

11. A method of removing particles from an aqueous feed stream comprising the step of contacting one side of a water wettable filter membrane as claimed in any one of claims 1 to 7 with the feed stream at a pressure sufficient to provide permeation.

12. The method according to claim 11, wherein the pressure is less than 10 bar.

Citation Information

Patent Citations

  • Preparation method for microporous membrane having multi-scale gradient micro-structure surface

    CN103611437A

  • Preparation method of microporous membrane with multi-scale gradient microstructure surface

    CN103611437B

  • Preparation method for mesoporous compound film

    CN106731886A

  • Dual Check Fuel Injector With Single Actuator

    US20140061326A1

  • Wireless power system

    US20150061591A1